(untitled) (Research, Society and Development, 2022)
Background: Visceral leishmaniasis (VL) is a neglected disease caused by species of the Leishmania donovani complex and transmitted mainly by the bite of infected sandflies. A less frequent form of transmission is the transfusion route, important in countries lacking screening procedures for VL in blood banks. Methods: To identify asymptomatic infection by Leishmania sp, our goal here was to evaluate and compare the performance of three different serological techniques: Flow Cytometry (FC); Direct Agglutination Test (DAT); and Immunoenzymatic Test (ELISA). Thirty-one asymptomatic carriers of L. infantum were selected, from a single blood bank located in Recife, northeastern Brazil. Results : Foi avaliada a frequência de amostras positivas assintomáticas nos testes, no ELISA baseado no antígeno solúvel de Leishmania (25,8%), FC (22,8%), DAT (9,7%) e ELISA baseado em uma única proteína recombinante (12,9%). A sensibilidade dos testes também foi avaliada, o FC (22,58%) e o ELISA com o antígeno solúvel (22,58%) apresentaram os maiores valores de sensibilidade que o DAT (6,45%) e o ELISA recombinante (12,9%). Apenas a CF apresentou baixa especificidade (22,22%), em contraste com as demais técnicas (100% de especificidade). Conclusion: Given the results presented, we highlight the low effectiveness of serological techniques for the identification of asymptomatic individuals, thus emphasizing the need to develop more accurate methods for this purpose.